Sistem Ekonomi Neoliberalis Kapitalisme Dalam Perspektif Nilai-Nilai Etik Islam - Umi Farihah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
The existence of the system of Capitalism in economic activity is now clearly cause damage everywhere. Capitalism as a system of philosophy is already disabled since birth, because he was born of the paradigm of secularism. As an alternative, Islam provides a solution for the damage that has occurred by applying economic system based on the revelation, namely Islamic Economic System.